The Use of Mind-Mapping to Improve Student’s Reading Comprehension At SMAN 1 Grati Pasuruan - Ayudyah, Saraswati; Sumarsono, Puji (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2017)
An Investigation on Team Teaching Implemented by Local and Foreign Teachers in Teaching English at SMAN 1 Ketapang Sampang